Harmonisasi Epistemologi Islam dan Regulasi Jaminan Produk Halal: Kerangka Konseptual Penguatan Daya Saing UMK Pasca-Keputusan BPJPH 2025 - Ali Imron Mashadi (FADZAT: Jurnal Ekonomi Syariah, 2025)
Regulatory transformation through the 2025 BPJPH Decision accelerates halal legality for Micro and Small Enterprises (MSEs) but risks creating administrative formalism that neglects ethical substance. This study aims to construct a conceptual framework harmonizing Islamic epistemology with technical regulations to strengthen MSE competitiveness. Using a critical conceptual review method, this study analyzes the gap between self-declare simplification policies and the challenges of modern food safety (novel food) and sustainability. The results indicate that MSE competitiveness cannot be built solely on certification subsidies but requires the integration of Maqasid al-Syari’ah values. The resulting conceptual framework positions the protection of life (hifz an-nafs) and the environment as new quality standards. It is concluded that harmonizing theological values and technical regulations can prevent "halal washing" and transform MSEs into ethically superior business entities in the global market.